2017
DOI: 10.1186/s12885-017-3442-y
|View full text |Cite
|
Sign up to set email alerts
|

Targeting MCL-1 sensitizes human esophageal squamous cell carcinoma cells to cisplatin-induced apoptosis

Abstract: BackgroundEsophageal squamous cell carcinoma (ESCC) is one of the most lethal malignancies in China and is an exceptionally drug-resistant tumor with a 5-year survival rate less than 15%. Cisplatin is the most commonly used conventional chemotherapeutic drug for the treatment of ESCC, but some patients have a poor response to cisplatin-based chemotherapy. New strategies that could enhance chemosensitivity to cisplatin are needed.MethodsWe used reverse transcription-RCR (RT-PCR), immunoblot, immunohistochemical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 50 publications
(73 reference statements)
1
43
0
Order By: Relevance
“…Anchorage-independent cell growth. The anchorage-independent cell growth assay was performed as described previously (18). Briefly, the Eagle's basal medium containing 10% FBS, 0.6% agar, and different concentration of xanthohumol was loading to a six-well plate as an agar base.…”
Section: Methodsmentioning
confidence: 99%
“…Anchorage-independent cell growth. The anchorage-independent cell growth assay was performed as described previously (18). Briefly, the Eagle's basal medium containing 10% FBS, 0.6% agar, and different concentration of xanthohumol was loading to a six-well plate as an agar base.…”
Section: Methodsmentioning
confidence: 99%
“…e soft agar assay was performed as described previously [27]. Briefly, 3 ml basal medium Eagle's medium containing 0.6% agar, 10% FBS, and various concentrations of ILQ was loaded into a 6-well plate.…”
Section: Soft Agar Assaymentioning
confidence: 99%
“…Studies have shown that Mcl-1 has anti-apoptotic actions by binding and sequestering pro-apoptotic proteins Bak and Bax to inhibit the initiation of the mitochondrial apoptotic pathway. 39,40 Mitochondrial apoptosis, also referred to as the intrinsic pathway, plays an irreplaceable role in I/R injury. After cerebral ischemia, the outer membrane of the mitochondria becomes permeable, and Cyt C is released from the mitochondria intermembrane space to the cytoplasm, thereby binding to the Apaf-1 and forming the apoptosome, which in turn activates caspase-3, eventually leading to irreversible apoptosis.…”
Section: Discussionmentioning
confidence: 99%